Lemmatisation of Adjectives in Sepedi - Gouws, R.H.; Prinsloo, D.J. (Lexikos, 1997)
One of the great challenges to compiling better dictionaries for the African languages is to develop sound strategies and procedures for planning the structure of the dictionaries. In this regard all the structural components of a dictionary, including the macrostructure, microstructure, mediostructure and access structure, come into play. Most dictionaries for African languages, including Sepedi dictionaries, fail even at this level. In this article the planning of especially the macrostructure in respect of one lexical category which has been unsatisfactorily treated in Sepedi dictionaries, namely the adjective, will be attempted. Secondly the lemmatisation of adjectives in six Sepedi dictionaries will be critically evaluated. This will be done with the emphasis on various metalexicographical aspects.